Recent Advances in the Construction of 2D Heterostructures for Electrocatalytic Water Splitting. Issue 11 (9th July 2022) - Quan, Quan; Ho, Johnny C.
Abstract : Two‐dimensional (2D) heterostructures, typically integrating two or more different components with well‐defined interfaces, have shown great prospects in energy storage and conversion applications owing to their unique structural merits and synergistic interface effects. This review provides a comprehensive overview of the rational construction of 2D heterostructures pertaining to electrocatalytic water‐splitting applications. The unique emphasis is given to the state‐of‐the‐art progress on synthesized strategies of various well‐organized 2D heterostructures. Moreover, the review offers insights into 2D heterostructures in electrocatalytic water splitting from the viewpoint of the structure–activity relationship using progressive examples. Finally, this review concludes with the potential challenges and prospects in the field, which may provide a guideline for developing more efficient 2D heterostructures to incentivize commercial implementation in this exciting research field. Abstract : In this review, important recent advances in 2D heterostructures are highlighted, from the various strategies for rational design and controllable synthesis to their efficient applications for electrocatalytic water splitting.